China's Transition to a New Phase of Development - Song, Ligang; Zhou, Yixiao (China Update Series, 2022)
The Chinese economy is currently undergoing fundamental changes. In this context, the 2022 China Update examines the key characteristics of China's transition towards a new phase of economic growth and development. This year's update book covers a range of diverse topics that reflect the complex and changing nature of the economy. It explores critical questions: Why does China need a new development paradigm, and what is the best way to achieve it? What are China's choices when faced with the restructuring of global industrial value chains? What key roles will domestic consumption play in the next phase of China's development? What does the digital transformation mean for the Chinese economy? What has been the domestic impact of the Covid-19 pandemic on income inequality and labour market outcomes? What pathways exist for China in its transition towards carbon neutrality? How does China's emissions-trading market compare with that of Europe? How will China's carbon neutrality strategy affect the Australian economy? What are the political factors influencing bilateral trade flows between China and its trading partners? And what is at stake for China-US relations?